High-temperature tensile mechanical behavior and ablation mechanisms of three-dimensional multi-directions braided carbon/boron-modified phenolic composites - Wentao Yang; Yang Jin; Zhengyan Yang; Diantang Zhang (Polymer Testing)
Three-dimensional (3D) braiding structures provide the solution strategy for both the high bearing capacity and low ablation of the new thermal protection systems. In this paper, two kinds of carbon/phenolic 3D braided composites, three-dimensional five-directional (3D5d) and three-dimensional six-directional (3D6d),were prepared. A combination of experimental and numerical simulations was used to reveal the Tensile damage mechanism of the materials at room (25 °C) and elevated (200 °C) temperatures. In addition, ablation tests of 3D5d and 3D6d were conducted for 30s and 60s. The results show that the high-temperature tensile mechanical behaviors and ablation mechanisms both exhibit the obvious structure effects. In detail, the tensile strength of 3D5d is 20.17 % and 17.86 % higher than those of 3D6d at room and elevated temperatures, respectively. The high-temperature tensile damage pattern of 3D5d includes shear fracture of braiding yarns, tensile fracture of fifth yarns, matrix softening and interfacial debonding. 3D6d has an additional sixth yarn tearing. Furthermore, the linear ablation rate, mass ablation rate, and crack volume fraction of 3D6d are 11.6 %, 13.9 %, 12.67 % lower than those of 3D5d after ablation for 60s. In 3D5d, ablation cracks extend along braiding yarns and fifth yarn. In contrast, 3D6d has additional cracks extending along sixth yarn.